1996
DOI: 10.1002/ana.410390318
|View full text |Cite
|
Sign up to set email alerts
|

Use of anti‐neurofilament antibody to identify paired‐helical filaments in inclusion‐body myositis

Abstract: Paired-helical filaments (PHFs) are an important diagnostic criterion of the inclusion-body myositis (IBM) muscle biopsy; but, until now, their presence could be identified only by electronmicroscopy. In this report, we describe an easy immunocytochemical procedure, utilizing commercially available antibody, that enables reliable identification of muscle PHFs by light microscopy. This procedure greatly facilitates diagnosis of IBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…We next examined the relationship between the Elk-1-positive deposits and those of SMI-31, a marker of IBM filaments. 8 The distribution and configuration of the Elk-1-positive deposits were the same as those of SMI-31 (see figure 4, lower row) in vacuolated fibers. Although SMI-31 also stained axons of IM nerves, as described previously, 21 anti-Elk-1 did not.…”
Section: Results Localization Of Mapks and Elk-1 In S-ibmsupporting
confidence: 53%
See 2 more Smart Citations
“…We next examined the relationship between the Elk-1-positive deposits and those of SMI-31, a marker of IBM filaments. 8 The distribution and configuration of the Elk-1-positive deposits were the same as those of SMI-31 (see figure 4, lower row) in vacuolated fibers. Although SMI-31 also stained axons of IM nerves, as described previously, 21 anti-Elk-1 did not.…”
Section: Results Localization Of Mapks and Elk-1 In S-ibmsupporting
confidence: 53%
“…It can also react with other proteins such as microtubule-associated protein (MAP) tau and MAP-2. 29 Because SMI-31 stains IBM filaments, 8 ERK and its target Elk-1 may be associated with the filaments or might be components of the filaments. Electron microscopic studies indicated that IBM filaments are largely cytoplasmic, and only occasional nuclei contain those filaments.…”
Section: Extracellular Signalregulated Kinase (Erk) and Elk-1 Immunolmentioning
confidence: 99%
See 1 more Smart Citation
“…11 All IBM biopsies showed muscle fibers with vacuoles on Engel trichrome staining 12 and 15-to 21-nm paired helical filaments (PHFs) by electron microscopy and by SMI-31 immunoreactivity. 13 In addition, all s-IBM patients had, in 60 to 80% of their vacuolated muscle fibers, Congo Red positivity using fluorescence enhancement. 14 …”
Section: Muscle Biopsiesmentioning
confidence: 98%
“…Several proteins found in amyloid plaques typical of AD accumulate in s-IBM muscle fibres, including apolipoprotein E (ApoE), α 1 -antichymotrypsin (α 1 -ACT), prion protein, hyperphosphorylated tau, presenilin 1, ubiquitin, β-amyloid (Aβ) and β-amyloid precursor protein [8, 9]. Moreover, tubulofilaments found in s-IBM resemble AD neurofibrillary tangles [10]. These points questioned the analogies in degenerative processes between AD and s-IBM [6].…”
Section: Introductionmentioning
confidence: 99%